The study of demand response programs for energy management in microgrids - Koh, Samantha Yuan Yun (2019)
The exponential growth of industries and population had resulted in the increasing trend of electricity consumption. This had eventually resulted in an increase in the generation to accommodate the necessary demand and demand response management is adopted to tackle the problem. The study of demand response for energy management in microgrids is an important element as it can be used to maintain demand and supply in balance to achieve cost efficiency or maintaining the system reliability. In this report, a numerical simulation will be performed over a load profile to make a comparison with a model where demand response program is incorporated. An evaluation will be presented to showcase the effectiveness of demand response while satisfying all the necessary limits and constraints imposed.